GLOBAL CITEZENSHIP EDUCATION MEMBENTUK MASYARAKAT CYBERCOMMUNITY - Ansori, Makruf; Talbase, Muaimin (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2018)
The global citizen education word if it is meant to mean global public education that aims to make global society more wise in menajalankan kehidupannnya and still in accordance with the norms of life. The term "Global Citizen" is also defined as the concept of global citizenship that challenges the human mind for a long time even though the exact definition can never really be agreed upon. So it is not surprising that global citezenship education can form cybercommunity because it is in this era of cyber society is growing rapidly and education for the global community is very necessary, especially moral education. Because in the present era has entered the name of a moral crisis that resulted in global society doing things beyond the norms and social values that exist. The global community must be able to fortify themselves so as not to fall into the negative impact that can harm yourself and all mankind. Keywords— Global Citizen Education, Cybercomunity